علاقة الصفات الشكلية لمنخري الأنف مع نموذج النمو الوجهي لدى البالغين (دراسة بواسطة الطبقي المحوري المخروطي) - جحجاح, يزن (Latakia University Journal -Medical Sciences Series, 2016)
Keeping the nasal morphology balanced with the other parts of the face and in harmony with the type of the facial growth constitutes one of the most challenging goals that have to be carefully considered in planning the Orthodontics and Dentofacial Orthopedic treatment. Nostrils are part of the soft tissue of the nasal respiratory system, which affect growth development of the craniofacial complex. Aim: to investigate the relationship of the Nostrils Morphology with Facial Growth Type in adults using Cone-Beam Computed Tomography (CBCT) scan. Materials and methods: 23 adult subjects (8 males, 15 females), were chosen from pretreatment patients undergoing orthodontic evaluation at the Department of Orthodontics and Dentofacial Orthopedics at Tishreen University and were ordinarily undergoing CBCT scan for non-orthodontics and for otolaryngology purpose. Cephalometric measurements determining facial growth type were performed according to Jarabak's analysis. Pearson's Correlation Coefficient was calculated to investigate the relationship between the CBCT nostrils measurements and Cephalometric measurements determining facial growth type. Results: The studied CBCT nostrils measurements have differences with statistical significance between the two genders. CBCT nostrils measurements have relationship with facial type growth. Conclusions Nostrils morphology appears to vary with the type of facial growth. يعتبر تحقيق توازن صفات شكلية مع بقية العناصر المكونة للوجه وإبقائها منسجمة مع نموذج النمو الوجهي تحدياً من أكثر التحديات صعوبة والتي يجب أن يتم أخذها بعين الإعتبار بحذر بالغ أثناء التخطيط للمعالجة في تقويم الأسنان والفكين، حيث يعد منخري الأنف جزء من النسيج الرخو المكون للجهاز التنفسي الأنفي الذي يؤثر على نمو وتطور المركب القحفي الوجهي هدف البحث: تحري وجود علاقة بين الصفات الشكلية لمنخري الأنف وبين نموذج النمو الوجهي وذلك لدى أفراد من البالغين باستخدام التصوير الطبقي المخروطي.مواد وطرق البحث: بلغ أفراد العينة 23 بالغاً (8 ذكور،15 أنثى) من مراجعي قسم تقويم الأسنان والفكين بكلية طب الأسنان بجامعة تشرين ولم يخضعوا لمعالجة تقويمية سابقة حيث تم انتقاؤهم من مرضى كانوا تلقائياً بصدد إجراء تصوير طبقي محوري مخروطي لأسباب لا تتعلق بمشاكل تقويمية أو بأمراض الأنف والأذن والحنجرة، تم إجراء دراسة سيفالومترية للنمو الوجهي وفق تحليل جاراباك، ومن ثم تحليل معامل ارتباط بيرسون لدراسة العلاقة بين قياسات منخري الأنف المجراة على صور الطبقي المحوري المخروطي مع القياسات السيفالومترية المحددة لنموذج النمو الوجهي.النتائج: قياسات منخري الأنف المجراة على صور الطبقي المحوري المخروطي تمتلك فروقات ذات دلالة إحصائية بين الجنسين، قياسات منخري الأنف المجراة على صور الطبقي المحوري المخروطي يمتلكان علاقة ذات دلالة إحصائية مع نموذج النمو الوجهي.الخلاصة: يبدو أن الصفات الشكلية لمنخري الأنف تتغير بتغير نوع نموذج النمو الوجهي.